Factibilidad para la creación del departamento de talento humano y su incidencia en el personal de la Unidad Educativa particular Abdón Calderón, Quevedo 2015 - Triviño de la Cueva, Andrea María (2015)
The present research work called feasibility THE CREATION OF THE DEPARTMENT OF HUMAN TALENT AND THEIR IMPACT ON STAFF OF THE PRIVATE EDUCATION UNIT ABDÓN CALDERON, QUEVEDO 2015", allowed preliminarily make the diagnosis of the current situation of UEPAC, than being a Education Media Unit high popularity at local, provincial level and has no UN Human Resource Department, that meets the needs of the administrative and teaching staff Institution. The investigation Perform market research, technical, economic - financial, Compliance Prior to demonstrate the feasibility of the project. Market research Through a field research carried out showed that the faculty and staff of the UEPAC, if required Human Resource Department, because no child labor needs met promptly. Technical, economic and financial studies yielded promising results for the creation of Human Resource Department, with what is expected that UEPAC, improve academic and administrative processes and the care given to Servers value is added. The introductory part of the project allowed to know the problem, which led to the statement of project objectives, the foundation theoretical, conceptual and legal theories of several authors who conducted the study validated are based. Methodology applied in the project, methods, types and Applied Research Methods and Procedures were reviewed, achieving the objectives. The results of the project brief market research, technical , economic and financial , the last chapters presented the conclusions drawn and recommendations raised in favor of the project as a contribution to the Directors of the UEPAC.